Pengaruh Model Pembelajaran Berbasis Masalah (PBM) dengan Pendekatan Scientific terhadap Kemampuan Pemecahan Masalah dan Kecerdasan Emosional (Lesson Study pada Mata Kuliah Statistik Elementer) - Fahrurrozi Fahrurrozi (Universitas Hamzanwadi, 2015)
This study aims to improve the quality of learning through Lesson study is to apply a problem-based learning (PBL) with a scientific approach in terms of problem solving skills and emotional intelligence. Implementation of Lesson study conducted in four cycles. Each cycle consists of three phases, namely the Plan (planning), Do (implementation), and See (reflection). The data obtained in the form of data and the implementation of Lesson study questionnaire on the learning outcome data that has been done, the data in a qualitative descriptive analysis. The data problem-solving skills and emotional intelligence questionnaire of students ware analyzed using multivariate and continued with univariate tests on the significance level of 5 %. The results of the questionnaire, the lesson is displayed as a percentage and can be summed up 100 % of the students gave the opinion that the implementation of learning interesting and motivated students will make but 30 % of students questioned the instruments are poorly understood. While the results of data analysis, showed that problem-based learning (PBL) with the Scientific approach positive effect in terms of problem-solving skills and emotional intelligence of students.